Construction of a new bivariate copula based on Ruschendorf method - Jin, Pauline Wee Mah; Shitan, Mahendran (Hikari, 2014)
Copula modelling is useful and popular in many areas of statistics like finance, hydrology, drought study, etc. Construction of new copula can be based on Ruschendorf method and in this study, we construct a new copula based on a function which consists of the component of exponential functions. We prove that this new copula satisfies all necessary properties of a copula. We have also studied some dependence properties of the newly constructed copula, namely, the Kendall's T, Spearman's p and tail dependence.